FCVARmodel.m: A matlab software package for estimation and testing in the fractionally cointegrated VAR - Morten Ørregaard Nielsen; Lealand Morin (Queen's University, Department of Economics, 2011)
This manual describes the usage of the accompanying freely available software package for estimation and testing in the fractionally cointegrated vector autoregressive (VAR) model.
Keywords: C22; C32; 330; cofractional process; cointegration rank; fractional autoregressive model; fractional cointegration; fractional unit root; VAR model; VAR-Modell; Wissenschaftliche Methode; Software; Schätztheorie